Powerful Pedagogy Self-Study of a Teacher Educator's Practice - Brandenburg, Robyn T. (Self-Study of Teaching and Teacher Education Practices, 2008)
Powerful Pedagogy: Self-Study of a Teacher Educator's Practice is the outcome of the author's systematically questioning her assumptions about teaching and, in various ways, gives voice to the many individuals who have had an impact on the development of the author's pedagogy as a mathematics teacher educator. Using self-study as both a lens and a methodology to research her practice over the past three years, the author examines the impact of reflection and reflective practice in pre-service teacher education; voice, silence and that which remains "unsaid"; the ways in which teacher identities emerge and develop, and the role of authority and power in learning about teaching. Pedagogy refers to the synergistic relationship which exists between learning and teaching - one informs and is impacted by the other. For me then, Powerful Pedagogy reflects the need to see teaching in new ways and to do so by placing inquiry at the centre of learning about the intricacies of teaching about teaching. Powerful Pedagogy is a "how-to-see-teaching-differently" book; one which identifies and raises for scrutiny and critique, the markers which help the learning about teaching as one attempts to enact a pedagogy of teacher education. Professor John Loughran, Foundation Chair, Curriculum & Professional Practice Associate Dean Faculty of Education Monash University (2007).